PERWUJUDAN KEADILAN BAGI ANAK LUAR KAWIN MELALUI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Rosalinda Elsina Latumahina (Universitas Airlangga, 2014)
By means of its decision number 46/PUU-VIII/2010, the Constitutional Court has made a breakthrough which intend to guarantee the fulfillment of civil rights for a child born out of wedlock from his/her both parents. By the fulfillment of civil rights, justice has been materialized for the child, as viewed from the perspective of the theory of justice.Keywords : civil rights, child born out of wedlock, justice.